Topographic Distribution of Amyloid-β, Tau, and Atrophy in Patients With Behavioral/Dysexecutive Alzheimer Disease. (5th January 2021) - Therriault, Joseph; Pascoal, Tharick A.; Savard, Melissa; Benedet, Andrea L.; Chamoun, Mira; Tissot, Cecile; Lussier, Firoza; Kang, Min Su; Thomas, Emilie; Terada, Tatsuhiro; Rej, Soham; Massarweh, Gassan; et al.
Abstract : Objective: To determine the associations between amyloid-PET, tau-PET, and atrophy with the behavioral/dysexecutive presentation of Alzheimer disease (AD), how these differ from amnestic AD, and how they correlate to clinical symptoms. Methods: We assessed 15 patients with behavioral/dysexecutive AD recruited from a tertiary care memory clinic, all of whom had biologically defined AD. They were compared with 25 patients with disease severity– and age-matched amnestic AD and a group of 131 cognitively unimpaired (CU) elderly individuals. All participants were evaluated with amyloid-PET with [ 18 F]AZD4694, tau-PET with [ 18 F]MK6240, MRI, and neuropsychological testing. Results: Voxelwise contrasts identified patterns of frontal cortical tau aggregation in behavioral/dysexecutive AD, with peaks in medial prefrontal, anterior cingulate, and frontal insular cortices in contrast to amnestic AD. No differences were observed in the distribution of amyloid-PET or atrophy as determined by voxel-based morphometry. Voxelwise area under the receiver operating characteristic curve analyses revealed that tau-PET uptake in the medial prefrontal, anterior cingulate, and frontal insular cortices were best able to differentiate between behavioral/dysexecutive and amnestic AD (area under the curve 0.87). Voxelwise regressions demonstrated relationships between frontal cortical tau load and degree of executive dysfunction. Conclusions: Our results provide evidence of frontal cortical involvement of tau pathology in behavioral/dysexecutive AD and highlight the need for consensus clinical criteria in this syndrome.